A new species of Trichopagurus de Saint Laurent (Crustacea: Decapoda: Anomura: Paguridae) from the Ryukyu and Yap Islands, and redescription of T. trichophthalmus (Forest) - Komai, Tomoyuki; Osawa, Masayuki (Zootaxa, 2005)
Discovery of a new hermit crab species from the Ryukyu Islands, Japan, led us to reexamine the holotype and supplemental specimens of Trichopagurus trichophthalmus (Forest), the type species of the heretofore monotypic Trichopagurus de Saint Laurent. Our examination has revealed that the gill lamellae of T. trichophthalmus are actually entire (= biserial), rather than shallowly divided distally (= quadriserial) as reported by de Saint Laurent (1970). The new species is assigned to Trichopagurus because of the 11 pairs of biserial gills, well-developed rostrum, moderately long male right sexual tube directed toward exterior, and the possession of a single left gonopore in female. The new species, T. macrochela n. sp., is distinguished from T. trichophthalmus primarily by the dorsoventrally flattened carpus with a distinctly delimited dorsomesial margin, less setose ambulatory legs, and markedly asymmetrical coxae of the female fifth pereopods, of which the left bears numerous setae on the ventral surface. It has been also shown that previous records of T. trichophthalmus from the Palau and Yap Islands are based on both true T. trichophthalmus and T. macrochela. A comparative, updated redescription of T. trichophthalmus is also provided.